“DEARLY”: multimedia learning application for dyslexia early reading intervention / Aina Suraya Musa - Musa, Aina Suraya (2020)
Dyslexia is one of the most common learning disabilities experienced by children and adults. Children with dyslexia have language learning disorder and this makes it difficult for them to master the skills to read, spell, and write. These children experience confusion regarding certain alphabets and without early intervention, it could negatively impact their learning and future. A large number of research had been conducted in exploring the benefits of technologies and information as a learning platform for individual especially children with dyslexia. Multimedia learning represents a word, text, graphic, video and animation. Past research have highlighted the use of multisensory approach when teaching dyslexic children to read. Additionally, phonics reading technique has proven its strength in helping these children to master literacy skills. With the advancement of learning strategies through the multimedia technology, this study seeks to integrate multisensory learning, QR code and phonic reading technique. This multimedia learning application is called “Dearly”. In this study, actual alphabet blocks have QR code stickers on them, which can be scanned via multimedia learning application. Then the learning application will display corresponding screen representing the alphabet. The learning application will allow children to recognize and visualize letters, words, sentences, and pronunciations in the Malay language.